Legal Status of the State Language in Lithuania after the Restoration of Independence - Dainius Žemaitis; Audrius Valotka (Lietuvių Kalba)
The Constitution of the Republic of Lithuania has established the highest official status of a language, i.e. a state language. Compliance with this status requires an appropriate legal framework and institutions that develop and enforce language policy and legislation.